KETERBACAAN MATERI CERITA RAKYAT PADA BUKU TEKS BAHASA INDONESIA KELAS X MENGGUNAKAN GRAFIK FRY - Annisa Rahma Anggraeni; Nur Ajizah Khasanah; Harsal Nikmah Febias; Roni Sulistiyono; Nia Ulfa Martha (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
This study aims to determine and describe the level of readability of folklore material in class X Indonesian textbooks. The main problem in this study is how the level of readability of folklore material in Indonesian class X textbooks, revision 2017, published by the Ministry of Education and Culture based on the graphic formula Fry? The subjects in this study were Indonesian class X textbooks, revision 2017, published by the Ministry of Education and Culture. In chapter 4 which is folklore material in the 2017 revised Class X Indonesian textbook, published by the Ministry of Education and Culture, there are 5 literary texts. The measurement of the level of readability in this chapter is measured through the five texts. This research is a type of qualitative research. The data analysis technique used in this research is a qualitative descriptive technique with data collection techniques in the form of library research. The measurements made in this study are based on Fry's graph theory. After conducting research to determine the level of readability using Fry's graph theory, it was found that the folklore material had a readability level that was not suitable for use in class X.